Viscoelastic Warpage and Stress Analysis in SIP Packaging: Numerical simulation and experimental validation - Ting-Yu Lee; Yu-Li Chen; Sheng-Jye Hwang; Chun-Yu Ko; Wei-Lun Cheng (Results in Engineering)
In this study, we use Moldex3D warpage and stress analysis to predict strip warpage by focusing on the PMC process and applying three distinct material models to ensure simulation accuracy, since deformation under high-temperature loading is highly sensitive to material behavior and demands precise modeling for reliable predictions.Simulation results show that the predicted warpage trend after molding exhibits a concave smiling shape, consistent with experimental results, with a maximum warpage value of 2.7 mm and approximately 10 % deviation compared to experimental measurements. Similarly, the predicted warpage trend after Post-Mold Curing (PMC) also displays a concave smiling shape, with a maximum warpage value of 1.0 mm and approximately 30 % deviation compared to experimental data.The 30 % error in warpage prediction after post-mold curing is primarily due to the simulation being conducted under ideal conditions, which are less influenced by external factors. Aside from the forces applied during transportation, other external disturbances, such as environmental variations and handling during production, also contribute to this noise, leading to the observed deviation.A series of simulations were conducted to investigate the effects of time and loading on strip warpage and the viscoelastic properties of EMC. The findings reveal that during high-temperature loading, the viscoelastic model significantly impacts deformation, causing gradual stress relaxation in the package. Changes in viscoelastic properties over time and temperature are essential factors determining the overall warpage behavior. According to the study, different EMC materials require varying PMC durations and temperatures to achieve the final relaxed modulus. Therefore, incorporating the viscoelastic model, the cure kinetics model, and the P-V-T-C model together during the PMC process is essential for accurate warpage prediction.These results highlight the importance of accurately modeling and employing appropriate material models to improve warpage prediction, thereby providing a valuable reference for optimizing packaging processes.